100 kBq m−3 Radon Activity Concentration in the Atmosphere of a Bathroom Supplied with Groundwater From A Gneissic Rock Area with Consanguineous Intrusions. Issue 6 (December 2016) - Søstrand, Per; Sverre, Langård; Danielsen, Tor Erik
Abstract : Abstract: Inhalation of escaping radon from groundwater comprises the largest part of radiological hazard from groundwater radionuclides in the uranium and thorium series. Groundwater containing 1.5 mg dm −3 uranium and 3 kBq dm −3 radon activity concentration supplied an ordinary bathroom of 15 m 3 in a home. Using the showerhead, atmospheric levels of radon activity in the bathroom exceeded 100 kBq m −3 within a period of about 1 h.